Effect of bonding agent ratio on mechanical and physical properties of natural rubber compounds for rubber to textile adhesion applications - Hidayat, Ade Sholeh; Arti, Dewi Kusuma; Utami, Wahyu Tri; Azahra, Siti Amalina; Anggaravidya, Mahendra; Saputra, Dita Adi; Gumelar, Muhammad Dikdik; Iskandar, Mohamad Sholeh; Taqwatomo, Galih; Fidyaningsih, Riastuti; Wisojodharmo, Lies Agustine; Husin, Saddam; et al. (Engineering and Applied Science Research, 2023)
This study aims to modify natural rubber (Hevea brasiliensis) into a compound for rubber-to-textile adhesion application using bonding agents, namely resorcinol (R) and hexamethylenetetramine (H). The composition variations of R and H were designed to be 0:0, 1:1, 1:2, and 1:3 for sample FRC-0, FRC-1, FRC-2, and FRC-3, respectively. The physical and mechanical properties, namely curing time, tensile strength, tear strength, elongation, shore A hardness, rebound resilience, density, abrasion resistance, and adhesion test based on ASTM D1876 were determined. The results of the adhesiveness test showed that the FRC-1 formulation with 1:1 ratio of R:H has a maximum load of 195.25 N with graphical observation indicated no displacement or debonding area. In case of FRC-2, it has a lower maximum load of 105.26 N with a displacement or debonding area indicated by graphical observation. The characterization results suggested that FRC-1 sample with 1:1 ratio of R:H, showed the optimum formulation for rubber-to-textile adhesion. It forms largest adhesive product and has outstanding physical and mechanical qualities, particularly in the peel test, which measures the effectiveness of rubber-textile bonding.